The wreckage of intentions : projects in British culture, 1660-1730 - Alff, David (Alembics., 2017)
The Wreckage of Intentions offers a comprehensive account of seventeenth- and eighteenth-century projects--concrete yet incomplete efforts to advance British society during a period defined by revolutions in finance and agriculture, the rise of experimental science, and the establishment of constitutional monarchy.